Functional Diversity of AAA+ Protease Complexes in Bacillus subtilis - Elsholz, Alexander K. W.; Birk, Marlene S.; Charpentier, Emmanuelle; Turgay, Kürşad (Frontiers in Molecular Biosciences, 2017)
Here, we review the diverse roles and functions of AAA+ protease complexes in protein homeostasis, control of stress response and cellular development pathways by regulatory and general proteolysis in the Gram-positive model organism Bacillus subtilis. We discuss in detail the intricate involvement of AAA+ protein complexes in controlling sporulation, the heat shock response and the role of adaptor proteins in these processes. The investigation of these protein complexes and their adaptor proteins has revealed their relevance for Gram-positive pathogens and their potential as targets for new antibiotics.